Losses Material Crushing Products Single Toggle Jaw Crusher - sumarjono, erry; Sukamto, Untung; Kadiman, Sugiarto (Retii, 2024)
Losses material or loss of material could occur in the mineral processing or mineral dressing, due to the crushing of excavated materials (material) resulting from mining in crushing or grinding. The amount of product produced using crushing equipment can always be smaller than the amount of feed inserted. This laboratory scale research was carried out to calculate the percentage of material loss. The research was carried out using a single toggle type jaw crusher. The feed that is put into the jaw crusher is 30 rock samples, the weight of each rock sample is weighed, expressed as the weight of the feed. Weighing is also carried out on the crushing results, expressed as product weight. Calculation of material loss is obtained from the difference between feed weight and product weight. The loss factor is calculated based on the difference in the weight of the feed and product compared to the weight of the feed. The percentage of material loss is calculated by reducing the weight of the product by the weight of the feed multiplied by 100%. The results of the research show that based on the average calculation the loss factor = 0.067320429 and the percentage of material loss = 6.732042886%. The conclusion obtained based on research on 30 data shows that the percentage of material loss in the rock crushing process using a single toggle jaw crusher is below 10%.